BSACI guideline for the diagnosis and management of allergic and non‐allergic rhinitis (Revised Edition 2017; First edition 2007). Issue 7 (7th July 2017) - Scadding, G. K.; Kariyawasam, H. H.; Scadding, G.; Mirakian, R.; Buckley, R. J.; Dixon, T.; Durham, S. R.; Farooque, S.; Jones, N.; Leech, S.; Nasser, S. M.; Powell, R.; et al.
Abstract: This is an updated guideline for the diagnosis and management of allergic and non‐allergic rhinitis, first published in 2007. It was produced by the Standards of Care Committee of the British Society of Allergy and Clinical Immunology, using accredited methods. Allergic rhinitis is common and affects 10–15% of children and 26% of adults in the UK, it affects quality of life, school and work attendance, and is a risk factor for development of asthma. Allergic rhinitis is diagnosed by history and examination, supported by specific allergy tests. Topical nasal corticosteroids are the treatment of choice for moderate to severe disease. Combination therapy with intranasal corticosteroid plus intranasal antihistamine is more effective than either alone and provides second line treatment for those with rhinitis poorly controlled on monotherapy. Immunotherapy is highly effective when the specific allergen is the responsible driver for the symptoms. Treatment of rhinitis is associated with benefits for asthma. Non‐allergic rhinitis also is a risk factor for the development of asthma and may be eosinophilic and steroid‐responsive or neurogenic and non‐ inflammatory. Non‐allergic rhinitis may be a presenting complaint for systemic disorders such as granulomatous or eosinophilic polyangiitis, and sarcoidoisis. Infective rhinitis can be caused by viruses, and less commonly by bacteria, fungi and protozoa.